The presence of clouds lowers climate sensitivity in the MPI-ESM1.2 climate model - A. Mosso; T. Hocking; T. Mauritsen (Atmospheric Chemistry and Physics)
Clouds affect the sensitivity of the climate system by changing their distribution, height, and optical properties under climate change. Although the precise magnitude remains uncertain, the direct cloud response to an external forcing is known to be destabilising. Additionally, clouds have a masking effect on CO2 forcing and can influence other feedback mechanisms such as the surface albedo feedback. To understand the overall impact of clouds, we compute how much the equilibrium climate sensitivity (ECS) to a doubling of CO2 changes when clouds are made transparent to radiation in an Earth system model (MPI-ESM1.2, the Max Planck Institute for Meteorology Earth System Model version 1.2). In practice, to stabilise the model climate at near-preindustrial temperatures, the solar constant was reduced by 8.8 %. Our experiments reveal that clouds exert a stabilising influence on the model, with a clear-sky ECS of 4.29 K, which is higher than the corresponding full-sky ECS of 2.84 K, contrasting with their direct destabilising effect. Detailed partial radiative perturbation diagnostics show that beyond directly amplifying warming by themselves, clouds also strengthen the negative lapse rate and positive water vapour feedbacks, while strongly damping the positive albedo feedback. These findings highlight the complex role of clouds in modulating climate sensitivity.